2021
DOI: 10.5327/z2447-212320212000113
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate requests for tumor markers in patients aged 50 years and older: lessons not learned

Abstract: OBJECTIVE: To investigate, within a private health insurance, the ordering frequency and the costs related to inappropriate TM test orders. METHODS: This study analyzed data regarding TM requests within a private health insurance between 2010 and 2017. Patients included in this analysis were ≥ 50 years old, had available medical records, and had at least 1 TM tested within the study period. Tests were considered inappropriate when TMs were used in screening for neoplasms, ie, when there was no previous diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This result is of particular interest since there are only very few studies examining partially this issue. For example, a Brazilian retrospective analysis based on healthcare claims data from 2010 to 2017 examined the medical specialty of ordering physicians and found that, interestingly, most of the physicians were cardiologists (23.9%) [46]. However, numbers of insured patients were rather low and only 1112 TM tests were analyzed in the whole period.…”
Section: Discussionmentioning
confidence: 99%
“…This result is of particular interest since there are only very few studies examining partially this issue. For example, a Brazilian retrospective analysis based on healthcare claims data from 2010 to 2017 examined the medical specialty of ordering physicians and found that, interestingly, most of the physicians were cardiologists (23.9%) [46]. However, numbers of insured patients were rather low and only 1112 TM tests were analyzed in the whole period.…”
Section: Discussionmentioning
confidence: 99%
“…Overuse of a wide range of tests including CT and MRI scans, blood tests and endoscopies also emerged as a common problem, causing harm and waste in limited-resource settings. Two recent studies, from Brazil44 and China45 identified rates of inappropriate ordering of tumour markers, both in excess of 50%, underscoring the need for better regulation of the use of emerging medical technologies. A small number of qualitative studies identified drivers of these problems including fear of litigation and conflicts with patients, financial incentives, and expanding disease definitions 30 32.…”
Section: Discussionmentioning
confidence: 99%
“…Second, oxidative stress differs according to age, the oxidative stress hypothesis of aging assumes that age-associated functional losses are due to the accumulation of reactive oxygen and nitrogen species-induced damage [ 27 ]. At the same time, oxidative stress is involved in several age-related illnesses, such as cardiovascular disease, chronic obstructive pulmonary disease, neurodegenerative diseases, chronic kidney disease, and cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%